Resilience: The role of accurate appraisal, thresholds, and socioenvironmental factors1. (2nd September 2015) - Southwick, Steven M.; Pietrzak, Robert H.; Charney, Dennis S.; Krystal, John H.
Abstract: Adding to the resilience model of Kalisch and colleagues, we suggest that resilience is associated with accurate rather than excessively positive or negative appraisal or reappraisal styles; that complex systems do not always change in linear fashion; that linkages of individuals, families, and communities markedly affect individual resilience; and that resilience research focus on specific factors or mechanisms as well as more global ones.